DEVELOPMENT OF QUICK RESPONSE CODE BASED LEARNING MODULE ON HUMAN REPRODUCTIVE SYSTEM MATERIALS TO INCREASE STUDENT LEARNING OUTCOMES. - Bella, Qothrinnida Anta; Miranda, Yula; Sunariyati, Siti (Journal Compound: Improving the Quality of English Education, 2022)
The objective of this research is to create a Quick Response Code equipped learning module on the human reproductive system that is applicable, doable, and efficient in enhancing student learning results. Students class XI from SMAN 3 Dusun Selatan served as the research subjects. research method Learning modules are created utilizing the ASSURE paradigm, which includes the following steps: (1) Analyze the Learner; (2) State Standards and Objectives; (3) Choose Methods; Media or Materials; (4) Utilize Media and Materials; (5) Require Learner Participation; and (6) Evaluate and Revise. The effectiveness of the instructional module and the students' cognitive learning results are both included in the observed data. Student learning outcomes were determined using the methods of observation, product assessment questionnaires, and tests. The results reveal that the module developed during this learning process received module assessments of 4.28 and 4.68 (feasible criteria were used) from material experts and media experts, respectively. It is possible to increase the module's effectiveness by The learning results for the experimental class's students were computed using the effectiveness formula, and they came out at (74.15%) in the very good effectiveness category. While students' learning results in the experimental class gain a score of 0.67 (medium category), those in the control class receive a score of 0.24. (low category). As a result, it can be said that the learning module created can effectively and practically increase student learning results.